2020
DOI: 10.5194/hess-2020-293
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Deforestation reduces the vegetation-accessible water storage in the unsaturated soil and affects catchment travel time distributions and young water fractions

Abstract: Abstract. Deforestation can considerably affect transpiration dynamics and magnitudes at the catchment-scale and thereby alter the partitioning between drainage and evaporative water fluxes released from terrestrial hydrological systems. However, it has so far remained problematic to directly link reductions in transpiration to changes in the physical properties of the system and to quantify these changes of system properties at the catchment-scale. As a consequence, it is difficult to quantify the eff… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2
2

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 102 publications
0
15
0
Order By: Relevance
“…Under continued global warming, precipitation and temperature extremes are expected to further increase and the hydrological cycle is likely to further accelerate (Allen et al, 2010;Kovats et al, 2014;Stephens et al, 2021). In addition, natural land cover change and anthropogenic activities of land-cover change and land-use management can substantially alter a catchment's water balance (Brown et al, 2005;Wagener, 2007;Fenicia et al, 2009;Jaramillo and Destouni, 2014;Nijzink et al, 2016a;Hrachowitz et al, 2020;Levia et al, 2020;Stephens et al, 2020Stephens et al, , 2021. Considering the unprecedented speed of change, Milly et al (2008) declared that stationarity is dead and no longer should serve as a default assumption in water management.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Under continued global warming, precipitation and temperature extremes are expected to further increase and the hydrological cycle is likely to further accelerate (Allen et al, 2010;Kovats et al, 2014;Stephens et al, 2021). In addition, natural land cover change and anthropogenic activities of land-cover change and land-use management can substantially alter a catchment's water balance (Brown et al, 2005;Wagener, 2007;Fenicia et al, 2009;Jaramillo and Destouni, 2014;Nijzink et al, 2016a;Hrachowitz et al, 2020;Levia et al, 2020;Stephens et al, 2020Stephens et al, , 2021. Considering the unprecedented speed of change, Milly et al (2008) declared that stationarity is dead and no longer should serve as a default assumption in water management.…”
Section: Introductionmentioning
confidence: 99%
“…The root-zone storage capacity is, therefore, the key element regulating the partitioning of water fluxes in many terrestrial hydrological systems. In addition, not only natural changes to the environment, but also human interference with vegetation affect transpiration water demand and hence the root-zone storage capacity (Nijzink et al, 2016a;Hrachowitz et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this method S r is derived from water storage deficit calculations in the root zone at catchment scale, assuming vegetation is able to keep memory of past deficit conditions to size roots in such a way to guarantee continuous access to water (hereinafter S r,MM ) (Gentine et al, 2012;Gao et al, 2014). Recent studies demonstrated that this method provides plausible catchmentscale estimates of S r (e.g., Gao et al, 2014;Nijzink et al, 2016;Wang-Erlandsson et al, 2016;Hrachowitz et al, 2020), that result in improvements in modelling catchment discharge compared to soil derived S r estimates (De Boer- Euser et al, 2016).…”
Section: Introductionmentioning
confidence: 99%